Temporal Ion Velocity Variation with Obliqueness in Magnetized Plasma Sheath - Adhikari, B. R.; Khanal, R. (Journal of Nepal Physical Society, 2021)
A narrow region having sharp gradients in physical parameters is formed whenever plasma comes into contact with a material wall. In this work, the temporal velocity variation of ions in such a sheath has been studied in the presence of an external oblique magnetic field. The Lorentz force equation has been solved for the given boundary conditions using Runge-Kutta method. In order to satisfy the Bohm criterion, ions enter the sheath region with ion acoustic velocity. It is observed that all components of the velocity waves are damped in plasma in the time scale of one second. The computed oscillatory part of ion velocity match with the equation of the damped harmonic oscillator. Thus obtained damping constants as well as the frequency of all three components are nearly equal for obliqueness less than 600 after which they are distinctly different. This is due to the fact that the magnetic field becomes almost parallel to the wall. In earlier studies, only the final velocity profiles are reported and hence this study is useful in understanding how the ion velocities evolve in time as they move from sheath entrance towards the wall.